COMPORTAMENTO INGESTIVO DE BOVINOS DE CORTE EM PASTEJO RECEBENDO UM ADITIVO FITOTERAPICO OU MONENSINA. - TEIXEIRA, Edvan Correia; SILVA, Gislaine Jara; SILVA, Camila de Souza; SANTOS, Marrony Gonçalves Pires; FERNANDES, Henrique Jorge (ANAIS DO ENIC, 2024)
-